Knowledge and perception about anesthesia and anesthesiologist in patients undergoing surgery in Nepal - Shrestha, Anil; Shrestha, Gentle Sunder; Acharya, Binita; Joshi, Pankaj; Bhattarai, Amit Sharma; Upadhyay, Binayak; Sah, Ram Pukar; Pradhan, Ritu; Ghimire, Ashish; Adhikari, Archan; Yadav, Rajesh; Bahadur Singh, Birendra; et al. (Grande Medical Journal, 2020)
Background: Anesthesia as a distinct specialty has evolved much beyond the boundaries of operation theater but the services are yet under-recognized. This may be partly because of the lack of knowledge about anesthesia and anesthesiologist in general public and also due to lack of effort to raise awareness among the general public. This study was done to assess the knowledge and perception about anesthesia and anesthesiologist in patients undergoing surgery in Nepal.Material and Methods: A total of 719 patients scheduled for elective or emergency surgery in eight hospitals of Nepal were consecutively recruited and interviewed using questionnaire at pre-operative period before evaluation by anesthesiologist or anesthesiology resident. Individual response to each question was graded using three point scale.Results: The age of the patients ranged from 16 to 87 with a mean of 39.5±15.7 years. Only 31.6% and 28.2% had previous surgery and anesthetic exposure respectively. The majority (69.4% and 49.8% respectively) had good knowledge about health care workers present in operation theater and the ones delivering anesthesia. However, knowledge about anesthesia types and anesthetic agents was poor in 48.4% and 51.9% respectively. The knowledge was poor about person responsible for monitoring and maintaining homeostasis (49%), person responsible for resuscitation (46.5%) and management of anesthesia related complications (49.5%). Remarkably, 48.3% of the respondents had average knowledge about who manages post-operative pain. The mean knowledge score for individual patient was calculated and, 11.1%, 83.4% and 5.4% had poor, average and good knowledge respectively.Conclusion: Majority of patients undergoing surgery had average knowledge and perception about anesthesia and anesthesiologist.